Description of Primary School Sanitation in Middle Insana Subdistrict Timor Tengah Utara District - Kefi, Vebronia Asterina; Sahdan, Mustakim; Boeky, Daniela L. A. (Timorese Journal of Public Health, 2022)
The availability of school sanitation such as clean water, latrines, CTPS, and trash bins is critical. Suppose the condition of school sanitation facilities and infrastructure does not meet health requirements. In that case, the lack of implementation of PHBS and lack of sanitation management in schools can harm student health. This study aims to determine the description of elementary school sanitation in Insana Tengah Subdistrict, Timor Tengah Utara District. This type of research is descriptive with a survey approach. The population in this study were all elementary schools in Insana Tengah Subdistrict, Timor Tengah Utara Regency, which amounted to 10 elementary schools. The results of the study at elementary schools in Insana Tengah Subdistrict, Timor Tengah Utara District showed that the condition of clean water was 100% eligible, 20% of latrine facilities were eligible, and 80% did not meet the requirements, 30% (CTPS) facilities were eligible and 70% did not meet the criteria, the condition of the 40% Garbage Disposal Facility were eligible and 60% does not meet the requirements, the behavior of using latrines to urinate/defecate many as 19 respondents (47%) have good behavior and 21 respondents (53%) have poor behavior, washing habitual behavior Hand with Soap 19 respondents (47%) had good behavior, and 21 respondents (53%) had poor behavior, waste management behavior was 20 respondents (50%) had good behavior and 20 respondents (50%) have poor behavior, (MKM) behavior many as three respondents (7%) have good behavior and 37 respondents (93%) have poor behavior, 30% School Sanitation Management has a suitable category, and 70% has a wrong variety. Therefore, it is expected for all school parties to pay attention to sanitation facilities and implementing PHBS in schools